Determinants of Audit Report Lag in State-Owned Enterprises - Rachman, Helmy Aulia; Fadila, Mutia; Rahma, Meilenia (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
Timeliness in submitting financial reports that have gone through the audit process is an important indicator for stakeholders for decision making. Therefore, this study aims to analyze the effect of industry type, company size and auditor switching on audit report lag with audit tenure as a moderating variable in State-Owned Enterprises listed on the Indonesia Stock Exchange for the period 2020-2022. This study uses secondary data sourced from the company's annual financial statements. The sample was taken using purposive sampling method, which consisted of 99 observational data analyzed through multiple linear regression and moderation regression using IBM SPSS software. The research findings show that industry type has a positive effect and company size has a negative effect on audit report lag. However, auditor switching has no effect on audit report lag, and audit tenure is unable to moderate the effect of industry type, company size, and auditor switching on audit report lag.